Prognostic implications of systemic immune-inflammation index and systemic inflammation response index in hemodialysis patients - Qianqian Zhu; Liang Dai (BMC Nephrology)
Abstract Objectives Patients undergoing hemodialysis (HD) face high mortality, mainly from cardiovascular disease (CVD), infections, and dialysis withdrawal. Systemic inflammation contributes significantly to these outcomes. This study aimed to examine the associations between the systemic immune-inflammation index (SII) and systemic inflammation response index (SIRI) with all-cause, CVD, and infection-related mortality in HD patients, and to evaluate their prognostic value. Methods We conducted a retrospective analysis of 1190 HD patients recruited between January 2012 and December 2016. Kaplan-Meier survival curves, Cox regression analysis, and restricted cubic spline (RCS) models were employed to explore the associations between SII, SIRI, and all-cause, CVD, and infection-related mortality. In addition, receiver operating characteristic (ROC) curves was used to determine the predictive accuracy of SII and SIRI. Results Among the 1190 patients (median age 62.0 years; 64.0% male), the all-cause mortality rate was 38.2%, while the CVD mortality rate was 16.9%. Adjusted Cox regression analyses revealed that patients in the highest SIRI quartile (quartile 4) had significantly elevated risks of all-cause (hazard ratio [HR] 2.29, 95% CI 1.38–3.80, P = 0.001), CVD (HR 3.78, 95% CI 1.43–10.01, P = 0.007), and infection-related mortality (HR 2.42, 95% CI 1.70–3.01, P < 0.001) compared to those in the lowest SIRI quartile. Similar associations were found for SII (P < 0.001). Kaplan-Meier curves demonstrated comparable results. RCS analysis revealed nonlinear relationships between SII, SIRI, and mortality risk (P < 0.05). ROC analysis highlighted that Both SII and SIRI demonstrated moderate to strong prognostic value, with SIRI consistently offering the best risk stratification. Conclusions Elevated levels of SII and SIRI are linked to higher risks of all-cause, CVD, and infection-related mortality in HD patients. SIRI appears to be a more reliable predictor of mortality risk. Future studies should explore the underlying mechanisms and validate the predictive value of SII and SIRI for mortality risk among HD patients. Clinical trail number Not applicable.